The development of an apoferritin-based artificial metalloenzyme for catalysis of sulfide oxidation - Hoteit, Camille (2018)
The development of artificial metalloenzymes is an expanding field, involving various protein scaffolds and incorporating a wide range of transition-metal catalysts. Due to its pH-dependent disassembling properties, apoferritin has been used extensively for various purposes. However, very few studies reported its use as a scaffold for the design of artificial metalloenzymes.